Use of the subclavian vessels for microvascular reconstruction in the vessel-depleted neck. Issue 1 (January 2021) - Broderick, D.; Vassiliou, L.; Kyzas, P.
Abstract: The previously treated neck is a serious problem if further free tissue transfer reconstruction is required. Vessel depletion is often a terrifying finding that creates the need for novel approaches to access vessels that lie outside the anatomical region of the head and neck. We present what is, to our knowledge, the first case of utilising the subclavian artery and vein in head and neck reconstruction. We describe the anatomical details and a step-by-step access approach, together with tips on how to perform safe and effective microvascular anastomoses. The quality of the subclavian vessels is excellent, and access to the area is straightforward provided it is carefully planned. The technique could be considered more often in the vessel-depleted neck.